Application of the TPR (Total Physical Response) model to Vocabulary Materials for Junior High School Students of Grade IX Darul U-Loom School, Satun, Thailand - Ardila Nurmala Sari; Syamsuyurnita Syamsuyurnita (Journal of General Education and Humanities, 2026)
Low mastery of Indonesian vocabulary among foreign-speaking students, characterised by achievement scores below the Minimum Completeness Criteria (KKM), low student participation, and the dominance of teacher-centred instructional methods, remains a major challenge in Indonesian language learning. This research aims to improve the Indonesian vocabulary skills of Grade IX students at Darul U-Loom School, Satun, Thailand, through the application of the Total Physical Response (TPR) model. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral design, comprising planning, action, observation, and reflection stages. The research subjects were 25 Grade IX students. The study was conducted through three stages: pre-cycle, cycle I, and cycle II. Data were collected through vocabulary tests, classroom observations, interviews, and documentation, and analysed using descriptive statistics and N-Gain analysis to measure the level of improvement in students’ vocabulary skills. The results revealed a significant improvement in students’ vocabulary mastery, as indicated by the increase in average scores from 56.40 in the pre-cycle to 67.20 in cycle I and 78.60 in cycle II. Learning completeness also improved from 36% to 88%, while the N-Gain analysis showed an increase from low (0.25) to medium (0.51). These findings indicate that the TPR model is effective in improving Indonesian vocabulary mastery and fostering more active, enjoyable, and meaningful learning for foreign-speaking students.